COMPARATIVE EVALUATION OF EFFICACY AND SAFETY OF TOPICAL METHOTREXATE WITH TRETINOIN VERSUS BETAMETHASONE WITH TRETINOIN IN PATIENTS OF ALOPECIA AREATA: A PROSPECTIVE RANDOMIZED DOUBLE-BLIND STUDY - SAROJ KOTHARI; VAIBHAV VIVEK KALGAONKAR; SANJAY KUMAR R; ANUBHAV GARG; RAJKUMAR ARYA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Alopecia areata (AA) is a reiterative and non-scarring type of hair loss that can affect any hairy area of the body, particularly the scalp. The present study is aimed at comparing the safety and efficacy of methotrexate with tretinoin versus betamethasone with tretinoin in patients of AA. Methods: A prospective and comparative study was carried out in 80 cases of AA in Gajra Raja Medical College, Gwalior (M.P.) from December 2022 to November 2023. Subjects were randomly allocated to two groups, namely, MXT and BMT, 40 patients in each group. In group MXT, patients were asked to apply methotrexate 1% gel in the morning and tretinoin 0.025% cream in the evening, and in group BMT patients were asked to apply betamethasone 0.05% cream once daily in the morning and tretinoin 0.025% cream in the evening for 6 months. Mean severity of alopecia tool (SALT) score, mean regrowth scale (RGS) score, and adverse drug reactions due to treatments were recorded at 0, 3, and 6 months. Results: Mean SALT score decreased from 4.40 to 0.57 in MXT and from 3.34 to 0.63 in BMT group after 6 months and is significant (p<0.05) from baseline values. MXT showed a better response, than BMT group but was not significant (p>0.05). RGS Grade 3 was observed in 13% of patients and RGS Grade 4 was observed in 87% of patients in MXT group patients. RGS Grade 3 was observed in 19% of patients and RGS Grade 4 was observed in 81% of patients in BMT group. On intergroup comparison, a greater number of patients treated with methotrexate and tretinoin showed RGS Grade 4 as compared to patients treated with betamethasone and tretinoin treated group but was not significant (p>0.05). Twenty-five patients in the MXT group and 17 patients in BMT group showed mild adverse drug reactions at the end of 1 month that included burning, itching, redness, stinging, folliculitis, and scaling and all were resolved with minor treatment. Conclusion: Topical methotrexate is more efficacious and equally safe as betamethasone, making it the first line of drug for the management of AA.